Barrett's oesophagus and oesophageal adenocarcinoma - Bird-Lieberman, E; Ford, H; Fitzgerald, R (2011)
Oesophageal adenocarcinoma has increased rapidly in the western world over the past 20 years. It is preceded by a condition Barrett's oesophagus in which the distal squamous epithelium is replaced by a columnar lined epithelium which is characterised histopathologically by gastric and intestinal cell types. The endoscopic and histopathological definitions continue to evolve over time. The risk of progression from Barrett's to adenocarcinoma is 0.6% per year and since symptomatic adenocarcinoma has a poor prognosis surveillance of Barrett's oesophagus is generally recommended in order to detect high grade dysplasia and intramucosal carcinoma lesions at an early curative stage. Endoscopic diagnostic and therapeutic technologies for early lesions are advancing rapidly. Screening is also being more seriously considered with the realisation that Barrett' oesophagus is a common condition and most cases are undiagnosed. Oesophageal adenocarcinoma is staged using a combination of CT and EUS and staging informs management which currently still mainly involves cytotoxic chemotherapy and oesophagectomy, although surgical techniques are becoming more minimally invasive to reduce morbidity. Molecular targeted therapies are beginning to be applied but this has lagged behind progress in other cancers. Curative and palliative treatment involves close liaison between members of the multidisciplinary team. © 2010 Elsevier Ltd. All rights reserved.